Needle and thread - Martin, Ann M., 1955-; Andreasen, Dan (New York : Scholastic, 2007)
Flora worries about her first Thanksgiving without her parents, while Ruby worries about getting a part in the school musical, and their new friends, Olivia and Nikki, are adjusting to big changes in their families.
Keywords: Thanksgiving Day -- Juvenile fiction; Sisters -- Fiction; Thanksgiving Day -- Fiction; Orphans -- Fiction; Grandmothers -- Fiction; Sixth-grade girls -- Fiction; Fourth-grade girls -- Fiction; Women business owners -- Fiction; Home (Concept) -- Fiction; Friendship -- Fiction; Children's theater -- Fiction; Loss (Psychology) -- Fiction; Small town life -- Fiction; Camden Falls (Imaginary place) -- Fiction; Theater -- Fiction; Family life -- Fiction; Thanksgiving Day -- Fiction; Theater -- Fiction; Family life -- Fiction; Friendship -- Fiction; Massachusetts -- Fiction; New England -- Fiction; Realistic fiction